Network analysis of the cerebrospinal fluid proteome reveals shared and unique differences between sporadic and familial forms of amyotrophic lateral sclerosis - Adam N. Trautwig; Edward J. Fox; Eric B. Dammer; Anantharaman Shantaraman; Lingyan Ping; Duc M. Duong; Caroline M. Watson; Fang Wu; Seneshaw Asress; Qi Guo; Allan I. Levey; James J. Lah; et al. (Molecular Neurodegeneration)
Abstract Background Amyotrophic Lateral Sclerosis (ALS), a neurodegenerative disease involving loss of motor neurons, typically results in death within 3–5 years of disease onset. Although roughly 10% of cases can be linked to a specific inherited mutation (e.g., C9orf72 hexanucleotide repeat expansion or SOD1 mutation), the cause(s) of most cases are unknown. Consequently, there is a critical need for biomarkers that reflect disease onset and progression across ALS subgroups. Methods We employed tandem mass tag mass spectrometry (TMT-MS) based proteomics on cerebrospinal fluid (CSF) to identify and quantify 2105 proteins from sporadic, C9orf72, and SOD1 ALS patients, asymptomatic C9orf72 expansion carriers, and controls (N = 101). To verify trends in our Emory University cohort we used data-independent acquisition (DIA-MS) on an expanded, four center cohort. This expanded cohort of 259 individuals included 50 sporadic ALS (sALS), 43 C9orf72 ALS, 22 SOD1 ALS, 72 asymptomatic gene carriers (59 C9orf72 and 13 SOD1) and 72 age-matched controls. We identified 2330 proteins and used differential protein abundance and network analyses to determine how protein profiles vary across disease subtypes in ALS CSF. Results Differential abundance and co-expression network analysis identified proteomic differences between ALS and control, as well as differentially abundant proteins between sporadic, C9orf72 and SOD1 ALS. A panel of proteins differentiated forms of ALS that are indistinguishable in a clinical setting. An additional panel differentiated asymptomatic from symptomatic C9orf72 and SOD1 mutation carriers, marking a pre-symptomatic proteomic signature of genetic forms of ALS. Leveraging this large, multicenter cohort, we validated our ALS CSF network and identified ALS-specific proteins and network modules. Conclusions This study represents a comprehensive analysis of the CSF proteome across sporadic and genetic causes of ALS that resolves differences among these ALS subgroups and also identifies proteins that distinguish symptomatic from asymptomatic gene carriers. These new data point to varying pathogenic pathways that result in an otherwise clinically indistinguishable disease.